Validation of the Croatian Version of Work Ability Index (WAI) in Population of Nurses on Transformed Item-Specific Scores - Smrekar Martina; Franko Alenka; Petrak Olivera; Zaletel-Kragelj Lijana (Sciendo, 2020)
To assess the psychometric properties of the Croatian version of a Work Ability Index Questionnaire (WAIQ-CRO) in the population of nurses by using a specific methodological approach.